Fungsi Filsafat Hukum dalam Pembentukan Hukum di Indonesia - Muhammad Khambali (UIN Sunan Kalijaga Yogyakarta, 2014)
Philosophy of Law seeks to examine ideas about the law that already exists oris to be held (legal establishment), see coherence, correspondence and legal functions arecreated,. Relation to Philosophy of Law against the legal establishment in Indonesia,that the Philosophy of Law was instrumental in shaping the direction of democratic law,leads to the essential needs of the community. The function of the national law is toprotect, then change the law or the establishment of Indonesia must go through theprocess of Legal Philosophy, in which is able to direct and accommodate the needs of lawin accordance with the progress of development in all fields, were also able to meet thediverse needs of the wider community, which established the rules for the game of life.Law established to regulate the behavior of members of the public. Most importantly,legally constituted as a fulfillment of a sense of justice for the wider community,regardless of race, class, ethnicity, party, religious, or other discrimination in theframework bhineka tunggal ika.